2020
DOI: 10.3390/rs12172837
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Sea Level Budget Assessment during the GRACE/Argo Time Period

Abstract: Sea level change is an important indicator of climate change. Our study focuses on the sea level budget assessment of the Arctic Ocean using: (1) the newly reprocessed satellite altimeter data with major changes in the processing techniques; (2) ocean mass change data derived from GRACE satellite gravimetry; (3) and steric height estimated from gridded hydrographic data for the GRACE/Argo time period (2003–2016). The Beaufort Gyre (BG) and the Nordic Seas (NS) regions exhibit the largest positive trend in sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Regionally variability in rates of sea-level rise have become an area of focus for recent studies 20 22 in part due to the advent of technology such as satellite altimetry, ARGO profile floats and GRACE + GRACE-FO. This has allowed us to investigate the major components of global mean sea-level individually and collectively as a sea-level budget.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regionally variability in rates of sea-level rise have become an area of focus for recent studies 20 22 in part due to the advent of technology such as satellite altimetry, ARGO profile floats and GRACE + GRACE-FO. This has allowed us to investigate the major components of global mean sea-level individually and collectively as a sea-level budget.…”
Section: Discussionmentioning
confidence: 99%
“… Data Type Details Length Source Reference Satellite Altimetry Daily Data Sea surface height above mean Sea Surface (‘sla’ sea-level anomaly). 0.25°*0.25° Gridded Dataset 1993–2019 Copernicus Climate Change Service (C3S): https://cds.climate.copernicus.eu/cdsapp#!/dataset/satellite-sea-level-global?tab=overview 32 , 33 Sea Surface Temperature European Centre for Medium-Range Weather Forecasts(ECMWF), ERA5 reanalysis of temperature of sea water near surface Monthly 0.25° × 0.25° Gridded Dataset 1993–2019 https://cds.climate.copernicus.eu/cdsapp#!/dataset/reanalysis-era5-single-levels-monthly-means?tab=overview 22 Salinity and Temperature World Ocean Atlas Climatology (WOA18) derived from objectively analysed and quality-controlled observations 1995–2004 https://www.ncei.noaa.gov/access/world-ocean-atlas-2018/ 34 , 35 Salinity and Temperature ARMOR 3D Reprocessed dataset of interpolated in-situ and satellite observed salinity and temperature data 0.25°*0.25° Gridded Dataset 1993–2019 https://data.marine.copernicus.eu/product/MULTIOBS_GLO_PHY_TSUV_3D_MYNRT_015_012/description 6 , 36 GRACE Gravity Recovery and Climate Experiment (GRACE, GRACE-FO). Mascon solutions of 1-arc-degree equal area cells 2002–2019 GFSC Laboratory (NASA) - https://earth.gsfc.nasa.gov/geo/data/grace-mascons 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea ice is instead slowly transported across the Arctic by the transpolar drift (Serreze et al, 1989), taking 1.5 to 3 years to travel from the Laptev Sea to Fram Strait (Pfirman et al, 1997;Steele et al, 2004). The transpolar drift and ice deformation rates have been observed to be accelerating since the early 2000s (Rampal et al, 2011;Spreen et al, 2011); just recently, the MOSAiC drift expedition has shown that the transpolar drift can, indeed, be unusually fast and thus is capable of rapidly transporting sea ice out of the Arctic (Krumpen et al, 2020).…”
Section: Sea Icementioning
confidence: 99%
“…Yet, various studies assessed trends and their underlying drivers in multiple observations of individual ECVs, often in combination with trends in reanalysis products, e.g., for precipitation (Zhang et al 2007), soil moisture (Preimesberger et al 2020), land evaporation (Zhang et al 2016b), and runoff (Yang et al 2019). Several recent studies demonstrated consistency in trends between a selection of water cycle ECVs, mostly between continental ice melt and sea level rise (Zemp et al 2019;Shepherd et al 2020;Raj et al 2020), but substantial uncertainty remains for the land water storage components (Cazenave et al 2018).…”
Section: Example Of Global Integration Of State-of-the-art Fluxesmentioning
confidence: 99%